Ilocutional Speech Actions to Indonesian Subject Teachers at SMA Negeri 1 Liwa Lampung Barat - Elisa Fitri (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: In the research that has been studied, this will get a deep understanding of illocutionary speech acts that interact in learning Indonesian at school. This researcher focuses on illocutionary speech acts. His research uses research in the form of qualitative and takes a study in the form of an ethnography of communication in order to examine an illocutionary speech act that exists in an appropriate situation. The results of this study explain that there are three components of illocutionary speech acts that are seen in the interaction of an Indonesian language lesson in class X IPS 2, namely assertive, directive, and commissive components. a research that has been compiled. Keywords: illocutionary speech acts, communication ethnography